Aerosol transport over the western Mediterranean basin: Evidence of the contribution of fine particles to desert dust plumes over Alborán Island. Issue 24 (31st December 2014) - Valenzuela, A.; Olmo, F. J.; Lyamani, H.; Granados‐Muñoz, M. J.; Antón, M.; Guerrero‐Rascado, J. L.; Quirantes, A.; Toledano, C.; Perez‐Ramírez, D.; Alados‐Arboledas, L.
Abstract Eight months (June 2011 to January 2012) of aerosol property data were obtained at the remote site of Alborán Island (35.95°N, 3.03°W) in the western Mediterranean basin. The aim of this work is to assess the aerosol properties according to air mass origin and transport over this remote station with a special focus on air mass transport from North Africa. For air masses coming from North Africa, different aerosol properties showed strong contributions from mineral dust lifted from desert areas. Nevertheless, during these desert dust intrusions, some atmospheric aerosol properties are clearly different from pure mineral dust particles. Thus, Angström exponent α(440–870) presents larger values than those reported for pure desert dust measured close to dust source regions. These results combine with α(440, 670) − α(670, 870) ≥ 0.1 and low single scattering albedo (ω(λ)) values, especially at the largest wavelengths. Most of the desert dust intrusions over Alborán can be described as a mixture of dust and anthropogenic particles. The analyses support that our results apply to North Africa desert dust air masses transported from different source areas. Therefore, our results indicate a significant contribution of fine absorbing particles during desert dust intrusions over Alborán arriving from different source regions. The aerosol optical depth data retrieved from Sun photometer measurements have been used to check Moderate Resolution Imaging Spectroradiometer retrievals, and they show reasonable agreement, especially for North African air masses.